THE EFFECT OF WATER TABLE DEEP TO TRUNK CIRCUMFERENCE RUBBER PB260 CLON AND SOIL CHEMISTRY OF PEAT SOIL IN MERANTI ESTATE RAPP OF RIAU - Sukariawan, Aries; Rauf, Abdul; Sutanto, Arief Setiawan; Santoso, Bolot (Jurnal Online Pertanian Tropik, 2015)
Study to evaluate the effect of the depth of water table in peatlands of the PB260 rubber girth immature plants (age 2-3 years) and chemical properties of peat soil has been carried out in Meranti Estate RAPP Kampar Estuary Pangkalan Kerinci District of Riau in December 2013. Research used descriptive method with measuring water table depth in selected plots with girth measurements of planting rubber trees planted in 2010 and 2011. At two sample plots (representing the shallowest water level and water level deep) dug each soil profile to the investigation and decision soil samples. Soil samples were analyzed at the Laboratory of BPTP North Sumatra. The results showed that the water table in peatlands deeper, reaching 88.6 cm girth will decrease the growth of young rubber trees. Rubber immature plants age 2 years who has the best girth growth in ground water at a depth of 29.6 cm deep and 3 years old trunk circumference rubber girth best growth at 65.3 cm water table. Water table is within reach mean 88.6 cm cause faster decomposition of peat soil is characterized by C/N ratio of lower and lower quality (fertility) peat soils with lower ash content, K-exchangeable, Mg-exchangeable, P-available and P-total.